Dental implant placement in a patient with cystinosis. A case report - Bretaudeau Clara; Paredes Francesca Siu; Sergheraert Johan; Massa Luciana; Laurence Sébastien; Diebold Marie-Hélène; Lefèvre Benoît; Mauprivez Cédric (EDP Sciences, 2018)
Introduction: Cystinosis is a rare genetic disease due to a defective transport of cystine out of the lysosomes, caused by a mutation of the gene encoding for the lysosomal carrier protein, the cystinosin. Cystine accumulation results in the formation of intracellular cystine cristals, that causes tissular and multi-organic lesions (kidney, eyes, endocrine glands). Observation: We report a rare case of a patient affected by infantile nephropathic cystinosis, who consulted for an implant placement in a single-tooth gap. Discussion: Accumulation of cystine leads to tissue damage, primarily in the kidney, the liver and the cornea, but other organs, such as the mouth, teeth and jaws may be also involved. The article aimed to present oral manifestations associated with this storage disease and to discuss how oral surgeon can evaluate and manage these patients despite the lack of a standardized protocol.